Applied Mycology - Rai, Mahendra;Ed. Bridge, Paul D;Ed (CABI, 2009)
This book is intended to provide both students and researchers with a broad background to some of the fastest developing areas in current applied mycology. A range of contributions are given to highlight the diverse nature of current applied mycology research. The opening chapter of this volume provides some examples of how mycology is often neglected, and presents a case for considering mycology as a megascience. The subsequent chapters have been loosely grouped into four sections in order to reflect the wider 'customers' or context of the particular mycological areas or activities. In each section, contributions that show either new applications or developments of well-established technology, or novel research into new technology or environments are included. The section on environment, agriculture and forestry is represented by contributions that illustrate novel fungal associations or new aspects of well-known interactions. The section on foods and medicine reflects the long history of applied mycology in the manufacture of alcoholic beverages, with two chapters devoted to beer production and winery spoilage issues. Chapters in the section on biotechnology and emerging science reflect some of the current interests in fungal enzymes and their importance in broader environmental processes and applications.